Aspects of the current problems of society in contemporary art - Olga Putecheva, Marzhan Yelubayeva, Andrey Mironov, Ludmila Kharchenko, (Opción, 2019)
The purpose of this article is to study and generalize the options for displaying the current problems of society in contemporary art via comparative qualitative research methods. As a result, the main content of contemporary art is not the work itself but the emotional reaction of the viewer to it, which sometimes causes shock and is a part of the author's task. In conclusion, the influence of contemporary art on the viewer is based on the method of translation of the idea inherent in the work